3D Bicontinuous Nanoporous Reduced Graphene Oxide for Highly Sensitive Photodetectors. (30th December 2015) - Ito, Yoshikazu; Zhang, Wenfeng; Li, Jinhua; Chang, Haixin; Liu, Pan; Fujita, Takeshi; Tan, Yongwen; Yan, Feng; Chen, Mingwei
Abstract : Reduced graphene oxide (RGO) is an important graphene derivative for applications in photonics and optoelectronics because of the band gap created by chemical oxidation. However, most RGO materials made by chemically exfoliated graphite oxide are 2D flakes. Their optoelectronic performance deteriorates significantly as a result of weak light‐matter interaction and poor electrical contact between stacking flakes. Here we report a bicontinuous 3D nanoporous RGO (3D np‐RGO) with high optoelectronic performance for highly sensitive photodetectors. 3D np‐RGO demonstrates a over 40 times higher light absorption than monolayer graphene materials and at least two orders of magnitude higher electron mobility than conventional RGO from discrete RGO flakes. The np‐RGO with an optimal reduction state shows ultrahigh photoresponse of 3.10 3 10 4 A W −1 at room temperature, approximately four orders of magnitude higher than graphene and other graphene derivatives at similar levels of light intensity radiations, and the excellent external quantum efficiency of 1.04 3 10 7 % better than commercial silicon photodetector. The ultrahigh capability of conversing photons to photocurrent originates from strongly enhanced light absorption, facilitated photocarrier transport, and tunable oxygenous defects and reduction states in the 3D interconnected bicontinuous RGO network. Abstract : 3D bicontinuous nanoporous reduced graphene oxide (3D np‐RGO) is developed for highly sensitive photodetectors. Ultrahigh photoresponsivity up to 3.10 × 10 4 A W −1 and external quantum efficiency as high as 1.04 × 10 7 % are observed, which result from strongly enhanced light absorption, facilitated photocarrier transport, and tunable oxygenous defects and reduction states in 3D interconnected bicontinuous np‐RGO network.